A tripartite approach to unearthing the duration of high temperature conditions versus peak metamorphism: An example from the Bunger Hills, East Antarctica - Tucker, N.; Hand, M.; Kelsey, D.; Taylor, Richard; Clark, Christopher; Payne, J. (Elsevier BV, 2018)
We present LA–ICP–MS U–Pb monazite and zircon geochronology, trace element chemistry and phase equilibria forward modelling to constrain the P–T–t evolution of the Bunger Hills, East Antarctica. Metasedimentary rocks in the Bunger Hills record evidence for a protracted metamorphic history during the Mesoproterozoic. Taken in isolation, zircon and monazite ages suggest an extremely long duration of high-temperature conditions (ca. 200 Myr). Calculated P–T models indicate metamorphism involved medium pressures of 5.5–7.1 kbar and high to ultrahigh temperatures of 800–960 °C, and that the P–T path likely tracked along a down-pressure to isobaric cooling trajectory. Integrating trace element data from zircon, monazite and garnet indicates that, despite the spread in U–Pb ages, peak metamorphism essentially occurred over the interval ca. 1220–1180 Ma. The age and conditions of Mesoproterozoic metamorphism are consistent with the high-grade metamorphic evolution proposed previously for Stage-2 of the Albany–Fraser Orogeny in southwestern Australia. The P–T–t conditions are interpreted to reflect extension, potentially associated with unloading and exhumation of a collisional orogen following Stage-1 of the Albany–Fraser Orogeny. This is the first study to integrate geochronology, trace element chemistry and P–T modelling to constrain the metamorphic evolution of the Bunger Hills and to interpret these constraints within the context of the now separate terranes of the Musgrave–Albany–Fraser Orogen. The three-way approach adopted in this study demonstrates that zircon and monazite may grow and modify through a number of processes. An integrated petrochronologic approach is therefore essential for investigations on high-grade terranes.